Exploring the Intersection of Religion and Culture: A Phenomenological Inquiry into the Cokaiba Tradition among the Fagogoru Community in Central Halmahera Regency - Alhadar, Muhdi; Rahmat, Rahmat; Assagaf, Fahima; Khitab, Wassam Muhammad (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
In sociological contexts, the interaction between culture and religious content naturally reflects the dynamic nature of social phenomena, arising from the harmonization of societal norms and religious principles. The Cokaiba tradition exemplifies this intersection, blending cultural heritage with Islamic commemoration. This study utilizes a phenomenological approach to explore the significance of the Cokaiba tradition within Halmahera society in North Maluku, aiming to elucidate broader perspectives on the interplay between culture and religion. Through qualitative research rooted in phenomenology, this study investigates the dynamics of the Cokaiba tradition within the Fagogoru Community in Central Halmahera, North Maluku. Data collection involves immersive engagement with key informants, including religious figures, community leaders, practitioners of the tradition, and local residents, through interviews, observations, and documentation. Findings reveal the emergence of Cokaiba as a fusion of cultural heritage and Islamic celebration, embodying principles of monotheism and serving as a means to propagate Islam within the region. Despite diverse interpretations, the convergence of religion and culture within Cokaiba fosters harmonious coexistence, facilitating the integration of religious values with cherished cultural practices. However, limitations include the challenge of fully capturing individual experiences and perceptions with a phenomenological approach and the potential lack of generalizability due to the study's focus on the Fagogoru Community. Future research incorporating a broader range of perspectives and cultural contexts would enhance understanding of the intricate dynamics between religion and culture manifested in traditions like Cokaiba.